Ethical consumption : a research overview - Hiller, Alex, 1977-; Goworek, Helen (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Arising from foundations in green and eco consumerism alongside corporate social responsibility, ethical consumption is a multi-disciplinary area of research, incorporating perspectives from marketing, psychology and sociology. This shortform book presents an expert overview of the empirical evidence on ethical consumption. It takes both an historical and thematic perspective, covering definitions of ethical consumption, typologies of ethical consumer practices, successes brought about from consumer action and an current challenges. It also focuses on the emergence of contemporary perspectives on ethical consumer behaviour from three discrete perspectives; those focusing on consumer segmentation (the profiling of ethical consumers), those which take a psychological approach (the decision-making processes which underpin ethical consumption), and those which are sociological in nature (the identities and practices which underpin ethical consumption). The book finally synthesises these perspectives in the context of the 'problems' that are often claimed to exist, such as the existence of the 'attitude-behaviour gap', and provides conclusions which make recommendations for practice and further research. It will be of interest to academics and students of marketing, consumption and related fields, as well as to practitioners and policy makers who want to understand more about the evidence pertaining to ethical consumers, what motivates them, and how to encourage and educate them to consume more ethically"--
Introduction -- Ethical Consumption: Definitions and Development -- Segmentation Perspectives on Ethical Consumption -- Psychological Perspectives on Ethical Consumption -- Sociological Perspectives on Ethical Consumption -- Problems in Ethical Consumption Research -- Conclusions: Observations on State of the Art.
Keywords: Consumption (Economics) -- Moral and ethical aspects; Consumer behavior -- Moral and ethical aspects; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Management